2014
DOI: 10.1177/0972150914535145
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Reliable and Valid Scale for Measuring Organizational Culture

Abstract: A number of survey instruments measuring organizational culture can be found in the literature. Many of these have been reported to suffer from construct and methodology related weaknesses. Specifically, these have been found to either have insufficient theoretical basis or result in a narrow depiction of the multidimensional construct of organizational culture. In this article, the authors report the construction of a scale for measuring organizational culture that starts with a sound theoretical model to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Ghosh and Srivastava [20] noted that the concept of organizational culture has been interpreted differently and not all complement or converge. After reviewing a sample of the literature on the instruments used in survey studies of organizational culture, the authors concluded that no two instruments were alike, and no two instruments shared a common theoretical basis.…”
Section: Cultural Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghosh and Srivastava [20] noted that the concept of organizational culture has been interpreted differently and not all complement or converge. After reviewing a sample of the literature on the instruments used in survey studies of organizational culture, the authors concluded that no two instruments were alike, and no two instruments shared a common theoretical basis.…”
Section: Cultural Dimensionsmentioning
confidence: 99%
“…Both studies found great variation in the definition and operationalization of organizational culture and its dimensions. Ghosh and Srivastava [20], based on Kluckhohn and Strodtbeck's [23] model, identified seven dimensions of organizational culture: (1) participation, (2) respect for individual, (3) attitude to risk, (4) attention orientation, (5) trust, (6) openness, and (7) power distance. Schein [15] in attempting to understand the content of a culture identifies some of its dimensions and presents questions to be asked regarding each dimension.…”
Section: Cultural Dimensionsmentioning
confidence: 99%
“…Many researchers define organizational culture as a set of values, beliefs, perceptions, assumptions, rules of conduct, practices, procedures, rituals, and symbols that typically define the way an organization does business (Ravasi & Schultz, 2006;Xiaoming & Junchen, 2012;Ghosh & Srivastava, 2014;Nguyen & Aoyama, 2014). Schein (2010) argues that organizational culture includes a range of structures, routines, rules and norms that direct or limit behavior.…”
Section: Organization Culturementioning
confidence: 99%
“…Based on the Organizational Culture Assessment Instrument (OCAI), there are four types of organizational culture, namely hierarchic (bureaucratic) culture, market culture, clan culture, and adhocratic culture (Zavyalova & Kucherov, 2010). Characteristics of organizational culture according to Ghosh (2014) consist of seven characteristics, namely: Trust, Openness, Freedom to experiment, Individualism (versus collectivism), Attitude towards constructive dissent, Participation and Result orientation. Ali Bavik (2014) conducted research in the field of the hospitality industry using qualitative methods with the development of definitions found based on the definition of organizational culture.…”
Section: Literature Reviewmentioning
confidence: 99%